2023
DOI: 10.1080/19490976.2022.2162306
|View full text |Cite
|
Sign up to set email alerts
|

The gut-microbiota-brain axis in a Spanish population in the aftermath of the COVID-19 pandemic: microbiota composition linked to anxiety, trauma, and depression profiles

Abstract: The prevalence of anxiety and depression soared following the COVID-19 pandemic. To effectively treat these conditions, a comprehensive understanding of all etiological factors is needed. This study investigated fecal microbial features associated with mental health outcomes (symptoms of anxiety, depression, or posttraumatic stress disorder (PTSD)) in a Spanish cohort in the aftermath of the COVID-19 pandemic. Microbial communities from stool samples were profiled in 198 individuals who completed validated, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 108 publications
(111 reference statements)
1
12
0
1
Order By: Relevance
“…Furthermore, our study reported that the familial transmission observed in the affective disorder also applies to the subgroup of those affected by the post-COVID-19 syndrome. Regarding physical symptoms, our results are in line with those documenting a relationship between depression and fatigue and pain in COVID-19 survivors [ 10 , 16 ], and those documenting alterations in microbiome [ 17 ]. In addition to these studies, we reported higher rates of cough, headache, anosmia, dysgeusia, red eyes, low vision, syncope, vertigo, Sjogren’s syndrome, dyspnea, chest pain, sore throat, rhinitis, and lack of appetite in subjects with depression.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, our study reported that the familial transmission observed in the affective disorder also applies to the subgroup of those affected by the post-COVID-19 syndrome. Regarding physical symptoms, our results are in line with those documenting a relationship between depression and fatigue and pain in COVID-19 survivors [ 10 , 16 ], and those documenting alterations in microbiome [ 17 ]. In addition to these studies, we reported higher rates of cough, headache, anosmia, dysgeusia, red eyes, low vision, syncope, vertigo, Sjogren’s syndrome, dyspnea, chest pain, sore throat, rhinitis, and lack of appetite in subjects with depression.…”
Section: Discussionsupporting
confidence: 90%
“…Mazza et al [ 10 , 16 ] also found a high level of fatigue and pain in COVID-19 survivors with depression. Post-COVID-19 syndrome’s associated depression has been also related to microbiome alteration [ 17 ] and higher incidence of gastrointestinal symptoms such as heartburn, constipation, diarrhea, and abdominal pain [ 18 ]. However, the reliability of the aforementioned studies is hampered by small sample sizes and the narrow range of post-COVID-19 syndrome’s symptoms that have been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Enterococcus also stimulates apoptosis of intestinal epithelial cells deprived of the protective mucus layer (Golińska et al, 2013 ) and might contribute to the pathway of “bacterial invasion of epithelial cells.” Meanwhile, the Christensenellaceae R-7 group could be the cause of the increased Escherichia-Shigella levels and was also identified as a biomarker in the feces of healthy participants with high abundance (Cai et al, 2023 ). Fusicatenibacter, Faecalibacterium , and Ruminococcus are healthy gut-associated butyrate-producing bacteria known to be beneficial to host immunity (Maruyama et al, 2022 ; Malan-Müller et al, 2023 ), and butyrate is an important regulator that reduces mucosal inflammation and strengthens the epithelial defense barrier (Canani et al, 2011 ). Furthermore, Holdemanella was positively correlated with C18-3OH, a compound known for its anti-inflammatory properties (Pujo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic microbiota produce harmful substances and inflammatory molecules in the gut, which then infiltrate into the brain, eventually causing neuroinflammation and cognitive impairment 114 . Gut–brain axis regulation is also reflected in some people with mental health disorders such as anxiety and depression, which are often accompanied by an abnormal abundance of gut microbiota, suggesting that intestinal flora disorder may also play a role in COVID‐19‐related anxiety and depression 115,116 . The potential causal relationship and processes between SARS‐CoV‐2 and gut microbiota alterations are shown in Figure 3.…”
Section: Dynamic Changes Of Microbiota In Covid‐19mentioning
confidence: 99%